Brav3let Enterprise / Nurul Jannah Fatehah Kamarul Zaman … [et al.] - Kamarul Zaman, Nurul Jannah Fatehah; Mohd Samsuri, Nur Zarif Sofea; Azman, Aina Faqihah; Ayub, Nur Anis; Azman, Muhammad Rusydi (2022)
Brav3let Enterprise is a company based in Kuala Lumpur that introduced a new multifunction bracelet. Our company provides a brand that offers a variety of multi-function bracelet designs for women and children. These bracelets can perform a variety of functions. While maintaining their sense of style, customers may avoid putting themselves or others in danger thanks to the designs integrated safety elements. Engineers at Brav3let Enterprise are responsible for the design as well as the maintenance of the alarm, GPS, and laser. The users are able to guarantee their own safety at any moment and in any location if they make use of this apparatus. The alarm that has been programmed into this bracelet is used to frighten away a potential kidnapper or snatcher from the wearer, as well as to safeguard the safety of women and children. Especially when your children are out shopping by themselves or when women are waiting for a bus at a bus stop. In addition to this, the GPS tracker has been outfitted with a button that can be found on its back, which allows parents to find out where their children are located at any given time and place. This bracelet features a built-in laser that can be directed at the eyes of the kidnapper as well as any other person. Because of this, even a brief exposure to a direct or reflected laser can cause irreparable eye damage because the eyes are much more sensitive to light than the skin or the rest of the body. Our company's aim and vision are to build a beautiful bracelet for safety, by inserting an alarm, a tracker, and a little torchlight beneath the brilliance of a diamond, and to guarantee the protection of both women and children. This will be our first product. Taking a more in depth look at the events that are taking place in modern times, such as the rising number of cases of snatching or abduction, among other things. Women and children are typically the only victims in these types of situations. This is because of the vulnerable nature of women and children, which makes them easy targets for predators. As a result, we craft this bracelet to both forestall the occurrence of such incidents in the future and lessen their frequency in the present. The location of Brav3let Enterprise, which can be found at G-064, Mid Valley Megamall, Lingkaran Syed Putra, Mid Valley City, 59200 Kuala Lumpur, is considered to be in the geographical centre of the city. As a result, the children, adolescents, and adult women who are 16 years of age or older and who attend school or live in the Kuala Lumpur area make up our primary target market. This position provides convenient access to public transportation, whether it be the MRT, LRT, or quick bus, and also, this location provides easy access to a major highway in Kuala Lumpur. This is a very strong corporate image in addition to having a very strategic position. Brav3let Enterprise has five employees. The company has a strong emphasis on increasing operational efficiency, which in turn lowers the cost incurred each unit. For instance, it might investigate ways to reduce the number of employees, implement novel procedures, and enhance the effectiveness of the supply chain. The question of how much the product itself costs to manufacture rather than the product itself is the primary focus here. As a result, this can have the effect of lowering prices for end users, but it also maintaining their product quality. The majority of businesses who follow this strategy do so on the condition that they are able to fully capitalise on economies of scale. It is not so practical for small specialised markets, such as phone cases that are adorned with diamonds. Instead, this tactic is typically utilised in mass marketplaces like retail and food services. The founders of Brav3let Enterprise each made a personal contribution to the business amounting to RM20, 000 and they also took out a loan from the bank to support the operation. All of the donations from our partners as well as the loans from the bank are being used toward supporting our start-up business capital and costs. In addition, we intend to use the funds to purchase all the necessary equipment to run the firm. In conclusion, we hope that our bracelet will be of benefit to anyone, particularly women and children who, due to their vulnerable nature, are more likely to be targeted by people who would like to kidnap or grab them. Because of the knowledge and experience of our staff, Brav3let is certain to enjoy satisfactory levels of revenue and profits throughout each year.